Real‐world outcomes with bortezomib‐containing regimens and lenalidomide plus dexamethasone for the treatment of transplant‐ineligible multiple myeloma: a multi‐institutional report from the Canadian Myeloma Research Group database. (9th February 2021) - Jimenez‐Zepeda, Victor H.; Venner, Christopher; McCurdy, Arleigh; Masih‐Khan, Esther; Atenafu, Eshetu G.; Sebag, Michael; Stakiw, Julie; Song, Kevin; LeBlanc, Richard; Reiman, Tony; Louzada, Martha; Kotb, Rami; et al.
Summary: Bortezomib‐containing regimens (BCRs) represented standard, first‐line therapy for transplant‐ineligible multiple myeloma (TIMM) in Canada until the introduction of lenalidomide and low‐dose dexamethasone (Ld). However, little comparative data exist to inform the selection of regimens. We assessed the outcomes for TIMM patients treated with cyclophosphamide, bortezomib and dexamethasone or prednisone (CyBorD/P), bortezomib, melphalan and prednisone (VMP), bortezomib and dexamethasone or prednisone (VD/P) and lenalidomide and low‐dose dexamethasone (Ld) using the Canadian Myeloma Research Group database. Of 1156 TIMM patients evaluated, 82% received bortezomib combinations while 18% received Ld. Median progression‐free survival (PFS) was 21·0, 21·1, 13·2 and 28·5 months ( P = 0·0002) and median overall survival (OS) was 52·0, 63·6, 30·8 and 65·7 months ( P < 0·0001) in the CyBorD/P, VMP, VD/P and Ld groups respectively. There was no significant difference in PFS and OS between the two triplet bortezomib regimens (VMP and CyBorD/P). Ld was associated with a longer PFS but not a significantly superior OS to date. Outcomes with the bortezomib‐steroid doublet were inferior (VD/P). However, multivariable analysis identified features related to disease biology as the most important prognostic factors for PFS and OS. Such factors, as well as those affecting the physician's choice of regimen, are likely to influence the results observed with different regimens. This study demonstrated real‐world outcomes in TIMM similar to those reported in clinical trials.